2011
DOI: 10.1007/s00267-011-9692-6
|View full text |Cite
|
Sign up to set email alerts
|

What’s Wrong with the Tap? Examining Perceptions of Tap Water and Bottled Water at Purdue University

Abstract: The environmental impacts of bottled water prompted us to explore drinking water choices at Purdue University, located in West Lafayette, IN. A random sample of 2,045 Purdue University students, staff, and faculty was invited to participate in an online survey. The survey assessed current behaviors as well as perceived barriers and benefits to drinking tap water versus bottled water. 677 surveys were completed for a response rate of 33.1%. We then conducted qualitative interviews with a purposive sample of uni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
170
1
5

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 135 publications
(198 citation statements)
references
References 10 publications
22
170
1
5
Order By: Relevance
“…"Environmental Concerns" was still robustly associated with drinking bottled water, given a correlation of −0.126 with p = 0.011. Furthermore, I tested the detailed factors of "Trust in Authority", "Barriers to Bottle Reuse", and "Self-Impact", which are examined in other literature [13,36,37]. The results also showed significant correlations of −0.1243, 0.140 and −0.126, respectively.…”
Section: Barriers To Bottle Reusementioning
confidence: 82%
See 1 more Smart Citation
“…"Environmental Concerns" was still robustly associated with drinking bottled water, given a correlation of −0.126 with p = 0.011. Furthermore, I tested the detailed factors of "Trust in Authority", "Barriers to Bottle Reuse", and "Self-Impact", which are examined in other literature [13,36,37]. The results also showed significant correlations of −0.1243, 0.140 and −0.126, respectively.…”
Section: Barriers To Bottle Reusementioning
confidence: 82%
“…Saylor et al conducted a mixed method research in Purdue University, US and assessed the current behaviors as well as the perceived benefits and barriers to drinking tap water versus bottled water [13]. They found that perceived risks from tap water and the perceived safety, preferred taste, and convenience of bottled water were major determinants.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In Madinah, KSA, and in almost all cities in the Gulf Cooperation Council (GCC) countries and around the world, drinking water is packed in plastic containers. The public should be advised to adapt to drinking tap water instead of bottled water (Saylor et al, 2011). It is also observed that all food and drinks prepared in some homes comes from bottled water as well.…”
Section: Discussionmentioning
confidence: 99%
“…Saylor et al [14] report that common barriers to drinking tap water include perceived risks of tap water and the perceived safety of bottled water, and the convenience of drinking bottled water. Results of the study carried out on Ferrara's PDRF help to highlight the weaknesses of these perceptions.…”
Section: Discussionmentioning
confidence: 99%
“…Many people are convinced that tap water is not good to drink, and bottled is perceived as safer, healthier and of better quality; however, there is no proof to confirm this [10,11]. Indeed, bottled water is not always better in quality than tap water, and the population's fear about public piped water is not justifiable [12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%